New forms of knowledge: Entrepreneurship and its connection with science and society - Fonseca, Marcello Pires; Filho, Wlademir Leite Correia; Souza, Alexandre Pirangy de; Souza, Karina Medeiros Pirangy de; Lima, Francisco Lucio Pinto de; Craveiro, Eliane Gonçalves; Colares, Cintya Barreiro; Fonseca, Marcio Pires; Fonseca, Kailey Ane dos Santos (Seven Editora, 2023)
Despite the lack of agreement, entrepreneurship has been investigated and its numerous elements in order to disseminate knowledge to all scholars and has also been researched by economists, sociologists, historians, psychologists and specialists in behavioral or management sciences. Thus, it can be shown that entrepreneurship has the status of an object of study in the social sciences due to its dynamic nature. The need to evaluate entrepreneurial research in the light of the theoretical and methodological issues inherent to social investigations arise in this scenario. These concerns address the debate about whether or not social research should be conducted using the same techniques as natural scientific research. The theoretical essay on the study of entrepreneurship in this monographic work discusses topics that show how the epistemological foundation of this phenomenon took place. With this, it is intended to highlight all the different aspects of this occurrence. DOI:https://doi.org/10.56238/interdiinovationscrese-055